Kierunki zmian systemów emerytalnych w nowych krajach członkowskich Unii Europejskiej - Klimkiewicz, Aldona (Transformation of pension systems in the EU new countries, 2006)
This article highlights alternative approaches to pension protection for retired workers in conditions of ageing populations. Nearly all of the new EU countries have increased their pensionable age and adopted new systems for voluntary supplemental pension savings. Some have scaled down their social insurance schemes in favour of new systems of commercially managed individual savings accounts. Most have enacted laws to encourage supplementation through voluntary schemes. Public pension formulas and contribution rates have been changed, some repeatedly. A large minority have adopted new methods for collecting contributions. The particular mix and pace of these changes have varied greatly from country to country. Some countries has transformed their systems in fundamental ways, altering the pooling of risks, the adequacy of benefits, and the management of revenues and information. Others are combining adjustments in their public pension systems with the development of voluntary supplemental retirement schemes. It will take decades for these new designs to be fully implemented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 197-205